The early black-figured pottery of Attika in context (c. 630-570 BCE) - Alexandridou, Alexandra-Fani, 1980- (Monumenta Graeca et Romana, 2011)
Setting as a starting point the introduction of the black-figure technique in Attic workshops at around 630 BCE, this book attempts a contextual analysis of Attic pottery until late in the first quarter of the sixth century BCE. The shapes and their functions, as well as the iconographic themes are explored through this perspective. This offers an interesting insight into funerary, cultic and profane activities in Athens and the Attic countryside, which is completed by an extensive study of the trade and distribution of Attic vases during this period. The result is a complete overview of early black-figure Attic production, enabling an afresh archaeological approach to late seventh-and early sixth-century Attic society.